2014
DOI: 10.1016/j.joen.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Activity of Porphyromonas endodontalis Complex Lipids

Abstract: Introduction Periapical infections secondary to pulpal necrosis are associated with bacterial contamination of the pulp. Porphyromonas endodontalis, a Gram-negative organism, is considered to be a pulpal pathogen. P. gingivalis is phylogenetically related to P. endodontalis and synthesizes several classes of novel complex lipids that possess biological activity, including the capacity to promote osteoclastogenesis and osteoclast activation. The purpose of this study was to extract and characterize constituent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…The colonization of P. endodontalis causes periapical lesions with acute symptoms, such as pain and swelling in response to purulent inflammation (Mirucki et al . ). Additionally, P. endodontalis induces inflammatory cytokines by stimulation with its lipopolysaccharide (Murakami et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The colonization of P. endodontalis causes periapical lesions with acute symptoms, such as pain and swelling in response to purulent inflammation (Mirucki et al . ). Additionally, P. endodontalis induces inflammatory cytokines by stimulation with its lipopolysaccharide (Murakami et al .…”
Section: Introductionmentioning
confidence: 97%
“…Porphyromonas endodontalis is a black-pigmented Gram-negative anaerobe associated with endodontic infections and pulp necrosis (Gomes et al 2008). The colonization of P. endodontalis causes periapical lesions with acute symptoms, such as pain and swelling in response to purulent inflammation (Mirucki et al 2014). Additionally, P. endodontalis induces inflammatory cytokines by stimulation with its lipopolysaccharide (Murakami et al 2001), and subsequent bone resorption can occur (Tang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was suggested that commensal Bacteroidetes, to which P. gingivalis belongs, that reside in the oral cavity and gut contribute to the pathogenesis of TLR2-dependent atherosclerosis through deposition and metabolism of serine dipeptide lipids in artery walls (6). In addition to P. gingivalis, the common dental pulpal pathogen Porphyromonas endodontalis produces the lipid 654 class (36). The lipid 654 preparations isolated from both Porphyromonas species were shown to promote osteoclast formation from RAW 264.7 cells (36), indicating that in addition to sub PG DHC lipids, osteoclast activation is promoted by serine dipeptide lipids and that the bacterial source of lipid 654 is probably not a critical issue.…”
Section: Pdhc and Serine Dipeptide Lipid Interference With Osteoblastmentioning
confidence: 99%
“…In addition to P. gingivalis, the common dental pulpal pathogen Porphyromonas endodontalis produces the lipid 654 class (36). The lipid 654 preparations isolated from both Porphyromonas species were shown to promote osteoclast formation from RAW 264.7 cells (36), indicating that in addition to sub PG DHC lipids, osteoclast activation is promoted by serine dipeptide lipids and that the bacterial source of lipid 654 is probably not a critical issue.…”
Section: Pdhc and Serine Dipeptide Lipid Interference With Osteoblastmentioning
confidence: 99%
“…Lipids are one of the four main macromolecules (along with nucleic acids, proteins and carbohydrates) essential for cells to function. Depending on their properties, lipids can have many roles in the cell including control of membrane structure and fluidity [ 4 , 5 ], signaling [ 6 ], facilitating membrane-associated functions [ 4 , 7 ], virulence [ 8 , 9 , 10 , 11 , 12 ] and drug resistance [ 4 , 13 , 14 ]. A great deal of research has been conducted to help better understand the role that lipids play in virulence across species and even within strains of the same species [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%